Tax incentives, ease of doing business and inflows of FDI in Africa: Does governance matter? - Adamu Braimah Abille; Sulemana Mumuni (Cogent Economics & Finance, 2023)
Apart from the corporate tax rates, the ease of doing business (EDB) index accounts for the cross-country or regional differences in the inflows of foreign direct investment (FDI) as established in the literature. However, this study contends that institutional quality indicators are critical to complement the role of the EDB in attracting the desired FDI into Africa. For empirical evidence, the study performs governance indicators-related step-wise system-GMM estimations of the effect of corporate tax, un-interacted EDB, and the interplay between EDB and governance indicators on the net inflows of FDI using data from 2015 to 2019 for 50 African countries. The findings show that the corporate tax rate and the un-interactive EDB have significant negative effects on the inflows of FDI in Africa in the short- and long runs. In contrast, governance indicators such as control of corruption, political stability, regulatory quality, rule of law, and government effectiveness complement EDB to exert positive effects on the inflows of FDI in Africa, albeit the findings are not generally significant. Tus, to attract the desired FDI, the study inter-alia calls for strict institutional quality assurance in Africa.
Keywords: 330; Africa; Ease of doing business; FDI; governance indicators; panel analysis